Current status and future plan of the Program of the Antarctic Syowa MST/IS radar (PANSY) - Sato, Kaoru; Tsutsumi, Masaki; Sato, Toru; Nakamura, Takuji; Saito, Akinori; Tomikawa, Yoshihiro; Nishimura, Koji; Kohma, Masashi; Hashimoto, Taishi (2019)
The Tenth Symposium on Polar Science/Special session: [S] Future plan of Antarctic research: Towards phase X of the Japanese Antarctic Research Project (2022-2028) and beyond, Tue. 3 Dec. / 2F Auditorium, National Institute of Polar Research conference object